Pre and post-monsoon seasonal variation of some heavy metal pollution in sediments of River Gomti in the Vicinity of Lucknow City, India - Chandra Sameer; K. Garg Sanjay (Journal of Applied Sciences and Environmental Management, 2017)
The concentration of heavy metals (Fe, As and Cu) was examine in riverbed sediments of Gomti river, Lucknow at selected sites in pre and post monsoon season for three consecutive years (2009-11). The concentration was ranged between (As: 0.07-0.7, Fe: 7462.00-7977.00, Cu: 10.98-36.73 μg g-1) in pre-monsoon and in post-monsoon metal concentration was ranged between (As: 0.05-0.07, Fe: 543.00-7797.00, Cu: 32.00-9. 23 μg g-1). Whereas Geo accumulation index (I geo), contamination factor (CF), US EPA guideline also apply to determine the readily toxicity. Fe and As pollution was found from negligible to low level while Cu leads from low to moderate pollution. Significant correlation found between the metals in pre and post-monsoon of studied years, in case of As it was found insignificant. Conservation and management plan is also suggest for contaminated sites.